Symptomatology and molecular diagnosis of banana streak virus disease. - Divya C R (Department of Plant Pathology ,College of Horticulture, 2011)
The banana (Musa spp.) is a crop of global importance in terms of income security to million of small farmers throughout the developing countries. It is the world's fourth most important commodity after rice, wheat and corn and is produced in tropical and subtropical regions. Banana is infected by several diseases caused by fungi, bacteria and viruses. Among the viral diseases, Banana streak is now emerging as a major disease affecting banana production world wide. This disease assumes significance as it affects plant growth, fruit yield and quality. It is also causing problems to germplasm exchange and in the certification of in vitro plantlets for international trade. The present project was undertaken to study the symptomatology of Banana streak disease, to investigate the role of root mealy bug - Geococcus sp. in the transmission of Banana streak virus, to standardize molecular indexing of planting materials of banana and to identify the source of resistance in the field gene bank. The symptoms of the disease appeared on different parts of the plant such as leaf lamina, midrib, pseudo stem and in bunches. On the leaf lamina, the symptoms developed as discontinuous or continuous linear small chlorotic streaks. These chlorotic streaks later turned necrotic, blackened and running perpendicular to the leaf axis extending from midrib to the leaf margin or sometimes form a linear mosaic like pattern on the lamina especially on older leaves. Dark brown coloured linear lesions appeared on other parts like petiole, midrib, pseudo stem, and on bunches. Under severe conditions, necrosis and death of cigar leaf was noticed. The plants showing such symptoms did not flower and resulted in 100 percent yield loss. The impact of the disease on biometric and yield characters was studied and observed that the disease affected the growth and yield of banana. A significant correlation was observed between the expression of symptoms with rainfall and temperature. The expression of the symptoms was more in cooler months and less in summer. The field gene bank comprising 290 accessions maintained at BRS, Kannara was screened to assess the reaction of these accessions to the disease. The disease incidence